Pelagic environments. - Jenkyns, H (Blackwell Scientific, 1986)
Pelagic sediments are chiefly composed of the microscopic skeletal remains of planktonic animals and plants, variously diluted by non-biogenic components. Such sediments may be carbonate-rich, silica-rich or clay-rich and they change in facies when traced laterally across the ocean and vertically through different bathymetric levels. The primary controls of these variations are the calcite compensation depth and the productivity of the near- surface waters. Various open-sea environments are outlined, divided on the basis of tectonics, topography and geography. -after Author